Motivasi pembentukan kecerdasan ganda (Multiple Question Development) berbasis pendidikan karakter pada siswa SMA/sederajat di Kota Makassar - Imam Suyitno; Manan Sailan; Heri Tahir (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The results of observations made on students who participated in the activities of the motivation to form multipleintelligences (Multple Question Development) showed that students had potential, but had not been able to develop the potentialof multiple intelligences possessed. So that many students are not aware that they have more potential in themselves. Based onthese considerations, we plan to conduct character education-based motivational activities in high school / equivalent students inMakassar City. This training activity is a preliminary activity. This means that participants are first given an understanding of thematerial and continue to develop their potential in an easy way. After this activity ended, the results were 266 students ofMakassar State Senior High School 10 following the implementation of motivational activities for the formation of multipleintelligences (Multple Question Development) based on character education. It is expected that this activity can increase themultiple intelligence (Multple Question Development) based on character education owned by students. Thus, it is expected tothe School, students and the Education and Culture Office of South Sulawesi Province to have an equal level of high school topay more attention and develop the potential of multiple intelligences owned by students so that later they can produce outputfrom high school / equivalent education units which is high in this globalization era, what's more to prepare for the goldengeneration of 2045.